Packaging adhesive film irradiated by low-energy electron beam and preparation method and application thereof

By adopting a multi-layer structure encapsulation film with low-energy electron beam irradiation, the problems of high cost, high process requirements and unstable EL of the main gate battery module encapsulation film are solved, and the effect of preventing dummy welding, hidden cracking and poor appearance of laminated components is achieved.

CN119709034AActive Publication Date: 2025-03-28CYBRID TECH(ZHEJIANG) INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411938461.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The packaging film materials of existing main gateless battery modules have high cost and high process requirements, resulting in welding tape displacement, dummy joints, EL unstable, and problems such as EL unstable and yellowing of the film in the aging test.

Method used

The multi-layer structure encapsulated film is irradiated by low-energy electron beams, including an irradiated crosslinking buffer layer and an adhesive layer. Through coextrusion integrated molding, the thickness of the irradiated crosslinking buffer layer and the melt index of the adhesive layer are controlled, so as to gradually reduce the pre-crosslinking degree from the buffer layer to the adhesive layer.

Benefits of technology

It effectively prevents the problem of dummy welding caused by excessive fluidity of the packaging film, avoids the problem of hidden cracking caused by excessive pre-crosslinking of the irradiated cross-linking buffer layer, and prevents the appearance of the laminated components caused by poor fluidity of the adhesive layer.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a packaging adhesive film adopting low-energy electron beam irradiation and a preparation method and application thereof. The packaging adhesive film comprises an irradiation crosslinking buffer layer and a bonding layer, the irradiation crosslinking buffer layer is prepared from the following raw materials in parts by weight: 100 parts of first EVA resin and 1-5 parts of a first auxiliary agent; the bonding layer is prepared from the following raw materials in parts by weight: 100 parts of second EVA resin and 1-5 parts of a second auxiliary agent; the thickness of the irradiation crosslinking buffer layer ranges from 0.05 mm to 0.35 mm. The melt index of the second EVA resin is 20 to 60 g / 10 min. According to the packaging adhesive film, one side of the buffer layer is irradiated by low-energy electron beams, so that the pre-crosslinking degree is gradually reduced from the adhesive film on the battery side to the adhesive film on the glass side, the problem of pseudo soldering is prevented, subfissure of the battery piece in the lamination process caused by overlarge overall pre-crosslinking degree of the irradiation crosslinking buffer layer is avoided, and the product quality is improved. And meanwhile, the problem of poor appearance of the laminated assembly caused by poor flowability of the bonding layer can be prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photovoltaic modules, and relates to a packaging film irradiated by low-energy electron beams, a preparation method and an application thereof, and specifically relates to a packaging film for a main-grid-free battery module irradiated by low-energy electron beams, a preparation method and an application thereof. Background Art

[0002] The busbar-free (0BB) technology refers to the process of eliminating the main grid and only printing the fine grid in the metal electrode screen printing process, and optimizing the width and spacing of the fine grid; using welding strips (wires) to replace the main grid and fit the fine grid to collect current and realize the interconnection of battery cells. The introduction of 0BB will have a more obvious cost-reduction and efficiency-increasing effect. The elimination of the main grid and the thinning of the secondary grid can greatly reduce the cost of silver paste consumption, and make the shading area smaller, ultimately increasing the overall power.

[0003] 0BB technology is still in the early stages of industrialization, and there are still a variety of process solutions on the market, mainly including SmartWire, glue dispensing, welding + glue dispensing and other solutions. The glue dispensing solution is to lay solder strips on the front and back of the cell (perpendicular to the grid line) and form a connection through glue, and cure the glue by light curing to make it more firmly adhere to the surface of the cell and the outside of the solder strip. The disadvantage of this solution is that there is a shadow under the solder strip during EL detection, and the bonding strength between the solder strip and the cell is insufficient. At present, the traditional photovoltaic encapsulation film on the market is too fluid, which easily causes the solder strip to shift during the lamination process, and the solder strip and the cell are prone to virtual connection.

[0004] At present, there are mainly the following methods for dispensing type busbar-free battery module packaging:

[0005] 1) Polyvinyl butyral resin (PVB) is used for encapsulation, which has high material cost, high lamination temperature requirements, high process requirements, and poor water vapor barrier performance;

[0006] 2) Encapsulation is performed through a double-layer structure (pre-cross-linked layer + non-pre-cross-linked layer), double-layer laying, complicated process and high cost;

[0007] 3) UV curing is used to give the film a certain degree of pre-crosslinking. This packaging method is EL unstable, the film turns yellow severely after UV aging, and the appearance defect rate of the laminated components is high.

[0008] Therefore, there is an urgent need in this field to develop a packaging film to solve the above-mentioned technical problems such as high packaging film material cost, high process requirements, EL instability caused by solder strip displacement and virtual connection, and EL instability and yellowing of the film during aging testing. Summary of the invention

[0009] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a packaging film irradiated by low-energy electron beams, a preparation method and application thereof, and specifically to provide a packaging film for a point-type main-grid-free battery assembly irradiated by low-energy electron beams, a preparation method and application thereof. The packaging film provided by the present invention has a multilayer structure, including an irradiation cross-linked buffer layer and an adhesive layer. The packaging film of the present invention is formed by co-extrusion integration, which has low cost and high operability. The low-energy electron beam is used to irradiate one side of the buffer layer, so that the pre-crosslinking degree from the battery side film to the glass side film is gradually reduced (that is, the pre-crosslinking degree from the buffer layer to the adhesive layer is gradually reduced), thereby preventing the packaging film from being too fluid, causing it to penetrate into the gap between the welding strip and the battery cell to form a cold weld, and avoiding the overall pre-crosslinking of the irradiation cross-linked buffer layer being too large, causing hidden cracks in the battery cell during the lamination process, and at the same time, it can prevent the problem of poor appearance of the laminated assembly caused by poor fluidity of the adhesive layer.

[0010] To achieve this object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a packaging adhesive film irradiated by low-energy electron beam, the packaging adhesive film comprising a radiation cross-linked buffer layer and an adhesive layer;

[0012] The raw materials for preparing the radiation cross-linked buffer layer include the following components in parts by weight: 100 parts of a first EVA resin, 1 to 5 parts of a first auxiliary agent (for example, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, etc.);

[0013] The raw materials for preparing the bonding layer include the following components in parts by weight: 100 parts of a second EVA resin, 1 to 5 parts of a second auxiliary agent (e.g., 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, etc.);

[0014] The thickness of the radiation cross-linked buffer layer is 0.05 to 0.35 mm (e.g., 0.05 mm, 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, etc.);

[0015] The melt index of the second EVA resin at 190° C. and 2.16 kg is 20 to 60 g / 10 min, for example, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, 40 g / 10 min, 45 g / 10 min, 50 g / 10 min, 55 g / 10 min, 60 g / 10 min, etc.

[0016] During use of the encapsulation film provided by the present invention, the radiation cross-linked buffer layer is in direct contact with the battery cell, and the bonding layer is in direct contact with the glass. By controlling the thickness of the radiation cross-linked buffer layer within a specific range, it helps to prevent the encapsulation film from having too fast fluidity and causing it to penetrate between the solder strip and the battery cell; by controlling the melt index of the EVA resin in the bonding layer within a specific range, it can prevent the laminated assembly from having a poor appearance.

[0017] In the present invention, the packaging film is irradiated with a low-energy electron beam, wherein the low-energy electron beam irradiation refers to an irradiation voltage of 100 to 300 KeV and a dose of 20 to 60 KGy.

[0018] Preferably, the thickness of the adhesive layer is 0.25-0.5 mm (eg, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, etc.) The present invention helps ensure the bonding strength between the adhesive layer and the glass and the normal lamination appearance by controlling the thickness of the adhesive layer within a specific range.

[0019] Preferably, the melt index of the first EVA resin at 190°C and 2.16kg is 2 to 30 g / 10min, for example 2g / 10min, 5g / 10min, 8g / 10min, 10g / 10min, 13g / 10min, 15g / 10min, 18g / 10min, 20g / 10min, 23g / 10min, 25g / 10min, 28g / 10min, 30g / 10min, etc., preferably 2 to 25g / 10min.

[0020] Preferably, in the first EVA resin, the VA content is 28-33%, for example, 28%, 29%, 30%, 31%, 32%, 33%, etc.

[0021] Preferably, the first auxiliary agent comprises the following components in parts by weight: 0.2-1.0 part of a crosslinking agent, 0.5-1.5 parts of a co-crosslinking agent, 0.2-1.0 parts of a silane coupling agent, 0.2-0.6 parts of a tackifier and 0.1-0.5 parts of a light stabilizer.

[0022] Preferably, in the first auxiliary agent, the amount of the crosslinking agent can be 0.2 part, 0.4 part, 0.6 part, 0.8 part, 1.0 part, etc.

[0023] Preferably, in the first auxiliary agent, the amount of the auxiliary cross-linking agent can be 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.3 parts, 1.5 parts, etc.

[0024] Preferably, in the first auxiliary agent, the amount of the silane coupling agent can be 0.2 part, 0.4 part, 0.6 part, 0.8 part, 1.0 part, etc.

[0025] Preferably, in the first auxiliary agent, the amount of the tackifier can be 0.2 parts, 0.4 parts, 0.6 parts, etc.

[0026] Preferably, in the first auxiliary agent, the amount of the light stabilizer can be 0.1 part, 0.3 part, 0.5 part, etc.

[0027] Preferably, the crosslinking agent includes any one of tert-butyl peroxy-2-ethylhexyl carbonate (TBEC), tert-amyl peroxy (2-ethylhexyl) carbonate (TAEC), diisopropylbenzene peroxide (DCP), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane or carbonyl peroxyacid-O,O-(1,1-dimethylpropyl)-O-(2-ethylhexyl) ester or a combination of at least two thereof.

[0028] Preferably, the auxiliary cross-linking agent includes any one of triallyl isocyanurate (TAIC), trimethallyl isocyanate (TMAIC), trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), pentaerythritol triacrylate (PETA), ethoxylated trimethylolpropane triacrylate (ethoxylated TMPTA) or propoxylated trimethylolpropane triacrylate (propoxylated TMPTA), or a combination of at least two thereof.

[0029] Preferably, the silane coupling agent comprises a combination of a first silane coupling agent and a second silane coupling agent.

[0030] Preferably, in the first auxiliary agent, the content of the first silane coupling agent is 0.1 to 0.5 parts by weight, for example, 0.1 parts by weight, 0.3 parts by weight, 0.5 parts by weight, etc.

[0031] Preferably, in the first auxiliary agent, the content of the second silane coupling agent is 0.1 to 0.5 parts by weight, for example, 0.1 parts by weight, 0.3 parts by weight, 0.5 parts by weight, etc.

[0032] Preferably, the first silane coupling agent includes any one or a combination of at least two of 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyltrimethoxysilane, 3-glycidylpropyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, triisostearoyltitanate isopropyl, isopropyltri(dioctylpyrophosphate)titanate, isocyanatepropyltrimethoxysilane, isocyanatepropyltriethoxysilane or 1,3,5-tris(trimethoxysilylpropyl)isocyanurate.

[0033] Preferably, the second silane coupling agent is a silane oligomer.

[0034] Preferably, the silane oligomer includes any one of 3-(methacryloyloxy)propyltrimethoxysilane oligomer, vinyltrimethoxysilane oligomer or vinyltriethoxysilane oligomer, or a combination of at least two thereof.

[0035] Preferably, the tackifier includes any one of toluene diisocyanate, isophorone diisocyanate, isophorone diisocyanate polymer, diphenylmethane diisocyanate, diphenylmethane diisocyanate polymer, hexamethylene diisocyanate or hexamethylene diisocyanate polymer, or a combination of at least two thereof.

[0036] Preferably, the light stabilizer includes any one of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (light stabilizer 770), poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) succinate or poly-{[6-[(1,1,3,3-tetramethylbutyl)-imino]-1,3,5-triazine-2,4-diyl][2-(2,2,6,6-tetramethylpiperidinyl)-nitrogen]-hexylene-[4-(2,2,6,6-tetramethylpiperidinyl)-amino]} or a combination of at least two thereof.

[0037] Preferably, the second auxiliary agent comprises the following components in parts by weight: 0.2-1.0 part of a crosslinking agent, 0.5-1.5 part of a co-crosslinking agent, 0.2-1.0 part of a silane coupling agent, 0.1-0.5 part of a light stabilizer, and 0.1-0.5 part of an ultraviolet light absorber.

[0038] Preferably, in the second auxiliary agent, the amount of the crosslinking agent can be 0.2 part, 0.4 part, 0.6 part, 0.8 part, 1.0 part, etc.

[0039] Preferably, in the second auxiliary agent, the amount of the auxiliary cross-linking agent can be 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.3 parts, 1.5 parts, etc.

[0040] Preferably, in the second auxiliary agent, the amount of the silane coupling agent can be 0.2 part, 0.4 part, 0.6 part, 0.8 part, 1.0 part, etc.

[0041] Preferably, in the second auxiliary agent, the amount of the light stabilizer can be 0.1 part, 0.3 part, 0.5 part, etc.

[0042] Preferably, in the second auxiliary agent, the amount of the ultraviolet light absorber can be 0.1 part, 0.3 part, 0.5 part, etc.

[0043] Preferably, the crosslinking agent in the second auxiliary agent includes any one of tert-butyl peroxy-2-ethylhexyl carbonate (TBEC), tert-amyl peroxy (2-ethylhexyl) carbonate (TAEC), diisopropylbenzene peroxide (DCP), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane or carbonyl peroxyacid-O,O-(1,1-dimethylpropyl)-O-(2-ethylhexyl) ester or a combination of at least two thereof.

[0044] Preferably, the auxiliary cross-linking agent in the second auxiliary agent includes any one of triallyl isocyanurate (TAIC), trimethallyl isocyanate (TMAIC), trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), pentaerythritol triacrylate (PETA), ethoxylated trimethylolpropane triacrylate (ethoxylated TMPTA) or propoxylated trimethylolpropane triacrylate (propoxylated TMPTA), or a combination of at least two thereof.

[0045] Preferably, the silane coupling agent in the second auxiliary agent comprises a combination of a first silane coupling agent and a second silane coupling agent.

[0046] Preferably, in the second auxiliary agent, the content of the first silane coupling agent is 0.1 to 0.5 parts by weight, for example, 0.1 parts by weight, 0.3 parts by weight, 0.5 parts by weight, etc.

[0047] Preferably, in the second auxiliary agent, the content of the second silane coupling agent is 0.1 to 0.5 parts by weight, for example, 0.1 parts by weight, 0.3 parts by weight, 0.5 parts by weight, etc.

[0048] Preferably, the first silane coupling agent in the second auxiliary agent includes any one or a combination of at least two of 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyltrimethoxysilane, 3-glycidylpropyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, triisostearoyltitanate isopropyl, isopropyltri(dioctylpyrophosphate)titanate, isocyanatepropyltrimethoxysilane, isocyanatepropyltriethoxysilane or 1,3,5-tris(trimethoxysilylpropyl)isocyanurate.

[0049] Preferably, the second silane coupling agent in the second auxiliary agent is a silane oligomer.

[0050] Preferably, the silane oligomer includes any one of 3-(methacryloyloxy)propyltrimethoxysilane oligomer, vinyltrimethoxysilane oligomer, vinyltriethoxysilane oligomer, and isocyanurate silane oligomer, or a combination of at least two thereof.

[0051] Preferably, the ultraviolet light absorber includes any one of 2-hydroxy-4-n-octyloxybenzophenone, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'bis(a,a-dimethylbenzyl)phenyl)benzotriazole, 2,4-bis(2,4-xylyl)-6-(2-hydroxy-4-n-octyloxyphenyl)-1,3,5-triazine, and 2,2-methylenebis[5-(1,1,3,3-tetramethylbutyl)-3-(1,3-dihydrobenzotriazole)phenol] or a combination of at least two thereof.

[0052] Preferably, the light stabilizer in the second auxiliary agent includes any one of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (light stabilizer 770), poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) succinate or poly-{[6-[(1,1,3,3-tetramethylbutyl)-imino]-1,3,5-triazine-2,4-diyl][2-(2,2,6,6-tetramethylpiperidinyl)-nitrogen]-hexylene-[4-(2,2,6,6-tetramethylpiperidinyl)-amino]} or a combination of at least two thereof.

[0053] In a second aspect, the present invention provides a method for preparing the encapsulation film according to the first aspect, the preparation method comprising the following steps:

[0054] The raw materials for preparing the radiation cross-linked buffer layer and the bonding layer are mixed respectively, co-extruded, cast into films, and then the radiation cross-linked buffer layer is pre-treated by electron beam irradiation to obtain the encapsulation adhesive film;

[0055] In the electron beam irradiation pretreatment, the irradiation parameters are as follows: the voltage is 100-300KeV (for example, 100KeV, 120KeV, 140KeV, 160KeV, 180KeV, 200KeV, 220KeV, 240KeV, 260KeV, 280KeV, 300KeV, etc.), and the dose is 20-60KGy, for example, 20KGy, 30KGy, 40KGy, 50KGy, 60KGy, etc.

[0056] In a third aspect, the present invention provides a use of the packaging film as described in the first aspect in a busbar-free battery assembly.

[0057] Preferably, the busbar-free battery assembly comprises a glue-point type busbar-free battery assembly.

[0058] Compared with the prior art, the present invention has at least the following beneficial effects:

[0059] The packaging film provided by the present invention adopts a special two-layer structure of a radiation cross-linked buffer layer and a bonding layer, which is co-extruded and integrated, has low cost and high operability, and adopts a low-energy electron beam to irradiate one side of the buffer layer, so that the pre-crosslinking degree from the buffer layer to the bonding layer is gradually reduced, which can prevent the packaging film from having excessive fluidity and thus penetrating into the gap between the welding strip and the battery cell to form a cold weld, and can also avoid the overall pre-crosslinking degree of the radiation cross-linked buffer layer being too large, causing hidden cracks in the battery cell during the lamination process, and at the same time can prevent the problem of poor appearance of the laminated component caused by poor fluidity of the bonding layer. DETAILED DESCRIPTION

[0060] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0061] Some raw material information of the specific implementation method of the present invention is as follows:

[0062] EVA resin, melt index is 6g / 10min, Sailbon UE2806;

[0063] EVA resin, melt index is 20g / 10min, Formosa Plastics 7670H;

[0064] EVA resin, melt index is 25g / 10min, Zhongke 2825;

[0065] EVA resin, melt index is 60g / 10min, SK EVA42-60;

[0066] 3-(Methacryloyloxy)propyltrimethoxysilane oligomer, Shandong SICO SICO-ON1743;

[0067] Hexamethylene diisocyanate polymer, Wanhua Chemical, HT-100.

[0068] Example 1

[0069] In this embodiment, a packaging adhesive film irradiated by low-energy electron beam is provided, wherein the packaging adhesive film comprises a irradiation cross-linked buffer layer and an adhesive layer;

[0070] The raw materials for preparing the radiation cross-linked buffer layer include the following components in parts by weight: 100 parts of EVA resin (Sailbon UE2806), 0.5 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.7 parts of triallyl isocyanurate, 0.8 parts of ethoxylated trimethylolpropane triacrylate, 0.2 parts of 3-methacryloxypropyltrimethoxysilane, 0.3 parts of 3-(methacryloxy)propyltrimethoxysilane oligomer, 0.2 parts of hexamethylene diisocyanate polymer and 0.1 parts of light stabilizer 770;

[0071] The raw materials for preparing the bonding layer include the following components in parts by weight: 100 parts of EVA resin (Zhongke 2825), 0.5 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.7 parts of triallyl isocyanurate, 0.8 parts of ethoxylated trimethylolpropane triacrylate, 0.2 parts of 3-methacryloxypropyl trimethoxysilane, 0.2 parts of isocyanate propyl triethoxysilane, 0.2 parts of ultraviolet light absorber 360 and 0.1 parts of light stabilizer 770.

[0072] The method for preparing the encapsulation film comprises the following steps:

[0073] The raw materials for preparing the radiation cross-linked buffer layer and the bonding layer are weighed by weight and mixed evenly, respectively put into two single-screw extruders of a co-extrusion casting machine, and melt-extruded into films to prepare a double-layer co-extruded film.

[0074] The double-layer co-extruded film is pre-crosslinked by electron beam radiation, and the electron beam irradiated surface is the irradiated crosslinked buffer layer. After irradiation, the packaging film is rolled up, and the irradiation parameters are voltage 200KeV and dose 30KGy. The thickness of the irradiated crosslinked buffer layer is 0.2mm, and the thickness of the adhesive layer is 0.3mm.

[0075] Example 2

[0076] The difference between this embodiment and embodiment 1 is that the components and amounts of the adhesive layer are different, as follows:

[0077] The raw materials for preparing the bonding layer of this embodiment include the following components in parts by weight: 100 parts of EVA resin (Formosa Plastics 7670H), 0.5 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.5 parts of triallyl isocyanurate, 0.6 parts of ethoxylated trimethylolpropane triacrylate, 0.2 parts of 3-methacryloxypropyltrimethoxysilane, 0.2 parts of 3-(methacryloxy)propyltrimethoxysilane oligomer, 0.2 parts of ultraviolet light absorber 360 and 0.1 parts of light stabilizer 770.

[0078] Example 3

[0079] The difference between this embodiment and embodiment 1 is that the components of the bonding layer are different, as follows:

[0080] The raw materials for preparing the bonding layer of this embodiment include the following components in parts by weight: 100 parts of EVA resin (SK EVA42-60), 0.5 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.7 parts of triallyl isocyanurate, 0.8 parts of ethoxylated trimethylolpropane triacrylate, 0.2 parts of 3-methacryloxypropyl trimethoxysilane, 0.2 parts of isocyanate propyl triethoxysilane, 0.2 parts of ultraviolet light absorber 360 and 0.1 parts of light stabilizer 770.

[0081] Example 4

[0082] The difference between this embodiment and embodiment 1 is that the irradiation parameters in the preparation method are different, specifically as follows: the irradiation parameters are voltage 200KeV, dose 40KGy.

[0083] Example 5

[0084] The difference between this embodiment and embodiment 1 is that the irradiation parameters in the preparation method are different, which are as follows: the irradiation parameters are voltage 150KeV and dose 50KGy.

[0085] Example 6

[0086] The difference between this embodiment and embodiment 1 is that the thickness of the radiation cross-linked buffer layer and the bonding layer are different, as follows:

[0087] The thickness of the radiation cross-linked buffer layer is 0.1 mm, and the thickness of the adhesive layer is 0.4 mm.

[0088] Example 7

[0089] The difference between this embodiment and embodiment 1 is that the components of the radiation cross-linked buffer layer are different, as follows:

[0090] The raw materials for preparing the radiation cross-linked buffer layer of this embodiment include the following components in parts by weight: 100 parts of EVA resin (Formosa Plastics 7670H), 0.5 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.7 parts of triallyl isocyanurate, 0.8 parts of ethoxylated trimethylolpropane triacrylate, 0.2 parts of 3-methacryloxypropyltrimethoxysilane, 0.3 parts of 3-(methacryloxy)propyltrimethoxysilane oligomer, 0.2 parts of hexamethylene diisocyanate polymer and 0.1 parts of light stabilizer 7700.

[0091] Example 8

[0092] The difference between this embodiment and embodiment 1 is that the components and amounts of the radiation cross-linked buffer layer are different, as follows:

[0093] The raw materials for preparing the radiation cross-linked buffer layer of this embodiment include the following components in parts by weight: 100 parts of EVA resin (Zhongke 2825), 0.5 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.7 parts of triallyl isocyanurate, 1.0 parts of trimethylolpropane triacrylate, 0.2 parts of 3-methacryloxypropyltrimethoxysilane, 0.3 parts of 3-(methacryloxy)propyltrimethoxysilane oligomer, 0.2 parts of hexamethylene diisocyanate polymer and 0.1 parts of light stabilizer 770.

[0094] Comparative Example 1

[0095] The difference between this comparative example and Example 1 is that the thickness of the radiation cross-linked buffer layer and the bonding layer are different, as follows:

[0096] The thickness of the radiation cross-linked buffer layer is 0.02 mm, and the thickness of the bonding layer is 0.3 mm.

[0097] Comparative Example 2

[0098] The difference between this comparative example and Example 1 is that the thickness of the radiation cross-linked buffer layer and the bonding layer are different, as follows:

[0099] The thickness of the radiation cross-linked buffer layer is 0.4 mm, and the thickness of the adhesive layer is 0.3 mm.

[0100] Comparative Example 3

[0101] The difference between this comparative example and Example 1 is that the irradiation parameters in the preparation method are different, as follows:

[0102] The irradiation parameters are voltage 400KeV and dose 30KGy.

[0103] Comparative Example 4

[0104] The difference between this comparative example and Example 1 is that the irradiation parameters in the preparation method are different, as follows:

[0105] The irradiation parameters are voltage 50KeV and dose 30KGy.

[0106] Comparative Example 5

[0107] The only difference between this comparative example and Example 1 is that no irradiation treatment is performed.

[0108] Comparative Example 6

[0109] The only difference between this comparative example and Example 1 is that the melt index of the EVA in the adhesive layer is 10 g / 10 min.

[0110] Comparative Example 7

[0111] The only difference between this comparative example and Example 1 is that the melt index of the EVA in the adhesive layer is 70 g / 10 min.

[0112] Comparative Example 8

[0113] The difference between this comparative example and Example 1 is that there is only a radiation cross-linked buffer layer, no bonding layer, and a single-layer structure.

[0114] The performance test of the encapsulation films provided in the embodiments and comparative examples is carried out in the following manner:

[0115] 1. Pre-crosslinking degree test:

[0116] a) Wash and dry the stainless steel mesh bag, weigh it and record it as W1 (accurate to 0.001g).

[0117] b) Cut the packaging film of the present invention into small particles of less than 3 mm×3 mm, weigh 0.5 g±0.01 g of the prepared sample, put it into a stainless steel wire mesh bag to make a sample package, and weigh it as W2 (accurate to 0.001 g).

[0118] c) Seal the sample bag with wire, mark it, and add it to the flask. Add 1 / 2 volume of xylene solvent to the flask, put a reflux condenser in the middle of the flask, and seal the excess opening with a rubber stopper. Heat until the xylene in the flask boils, reflux for 5 hours, and keep the reflux rate at 30 drops / min.

[0119] d) After the reflux is completed, take out the sample package, put it into an oven, control the temperature at 140°C, and dry it for 3 hours.

[0120] e) Take the sample package out of the oven, remove the iron wire, cool it to room temperature, and weigh it to record it as W3 (accurate to 0.001g).

[0121] f) Calculate the pre-crosslinking degree D according to the following formula:

[0122] 2. Appearance of laminated components

[0123] Put them into a vacuum laminator in the order of "glass / encapsulation film of the present invention / cell / encapsulation film of the present invention / glass", evacuate for 5 minutes at 145°C, and observe whether there are bubbles on the appearance after lamination for 10 minutes. It is judged as OK if there are no bubbles; the adhesive layer in the encapsulation film of the present invention contacts the glass surface, and the radiation cross-linked buffer layer contacts the cell surface.

[0124] 3. EL (electroluminescence) after lamination

[0125] The components were placed in a vacuum laminator in the order of “glass / encapsulation film of the present invention / cell / encapsulation film of the present invention / glass”, vacuumed for 5 minutes and laminated for 10 minutes at 145°C. The laminated components were tested for EL according to the IEC 61215 test standard. If there was no shadow on the EL, it was judged to be OK.

[0126] 4. TC200 rear EL test

[0127] Place the components in test 3 into a high and low temperature cycle test chamber. After TC200, test the EL of the components according to the IEC 61215 test standard. The experimental conditions are -40℃~85℃ (one cycle is not less than 5h). The experimental time is 200 cycles. After TC200, the EL test of the components is <3%, which is judged as OK.

[0128] The performance test results are shown in Table 1.

[0129] Table 1

[0130] Pre-crosslinking degree % Component appearance EL after lamination TC200 rear EL test Example 1 15 OK OK OK Example 2 15 OK OK OK Example 3 13 OK OK OK Example 4 19 OK OK OK Example 5 18 OK OK OK Example 6 12 OK OK OK Example 7 14 OK OK OK Example 8 15 OK OK OK Comparative Example 1 8 OK With shadow With shadow Comparative Example 2 30 There are bubbles and the battery is cracked OK OK Comparative Example 3 21 There are bubbles OK OK Comparative Example 4 10 OK With shadow With shadow Comparative Example 5 0 OK With shadow With shadow Comparative Example 6 18 There are bubbles OK OK Comparative Example 7 14 Battery Cell Parallel OK With shadow Comparative Example 8 22 There are bubbles OK OK

[0131] It can be seen from Table 1 that the encapsulation films provided by the embodiments of the present invention all have good appearance, no bubbles, no hidden cracks in the battery cells, and no shadows after lamination and TC200.

[0132] It can be seen from Example 1, Comparative Example 1 and Comparative Example 2 that if the radiation cross-linked buffer layer is too thin, the film fluidity will be large, resulting in poor soldering between the solder ribbon and the battery cell, and EL will have shadows after lamination; if the radiation cross-linked buffer layer is too thick, it will lead to the appearance of unmelted bubbles.

[0133] It can be seen from Example 1, Comparative Example 3, Comparative Example 4 and Comparative Example 5 that the adjustment of irradiation parameters will affect the pre-crosslinking degree. High irradiation energy will cause bubbles in the laminated component, and low irradiation energy will cause shadows in the EL of the laminated component.

[0134] It can be seen from Example 1, Comparative Example 6 and Comparative Example 7 that the melt index of the adhesive layer resin has a great influence on the appearance of the laminated component. If the melt index is too low, there will be bubbles on the appearance of the component during lamination. If the melt index is too high, there is a risk of cell stacking during lamination.

[0135] The packaging film provided in Comparative Example 8 only has a radiation cross-linked buffer layer and no adhesive layer, and bubbles appear on the appearance of the component during lamination.

[0136] In summary, the packaging film for the main-grid-free battery assembly of the present invention adopts low-energy electron beam irradiation on one side of the buffer layer, so as to achieve a gradual decrease in the degree of pre-crosslinking from the buffer layer to the bonding layer, which not only prevents the packaging film from having excessive fluidity and causing it to penetrate into the gap between the welding strip and the battery cell to form a cold weld, but also avoids the overall pre-crosslinking degree of the irradiated cross-linked buffer layer being too large, causing hidden cracks in the battery cell during the lamination process, and at the same time prevents the problem of poor appearance of the laminated assembly caused by poor fluidity of the bonding layer.

[0137] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the packaging film irradiated by low-energy electron beams and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A packaging film irradiated by low-energy electron beam, characterized in that: The packaging film includes a radiation cross-linked buffer layer and a bonding layer; The raw materials for preparing the radiation cross-linked buffer layer include the following components in parts by weight: 100 parts of a first EVA resin and 1 to 5 parts of a first auxiliary agent; The raw materials for preparing the bonding layer include the following components in parts by weight: 100 parts of a second EVA resin and 1 to 5 parts of a second auxiliary agent; The thickness of the radiation cross-linked buffer layer is 0.05 to 0.35 mm; The melt index of the second EVA resin at 190° C. and 2.16 kg is 20 to 60 g / 10 min.

2. The packaging film according to claim 1, characterized in that: The thickness of the bonding layer is 0.25 to 0.5 mm; Preferably, the melt index of the first EVA resin at 190° C. and 2.16 kg is 2 to 30 g / 10 min, preferably 2 to 25 g / 10 min; Preferably, the content of VA in the first EVA resin is 28-33%.

3. The packaging film according to claim 1 or 2, characterized in that: The first auxiliary agent comprises the following components in parts by weight: 0.2 to 1.0 parts of a crosslinking agent, 0.5 to 1.5 parts of a co-crosslinking agent, 0.2 to 1.0 parts of a silane coupling agent, 0.2 to 0.6 parts of a tackifier and 0.1 to 0.5 parts of a light stabilizer.

4. The packaging film according to claim 3, characterized in that: The cross-linking agent includes any one of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy (2-ethylhexyl) carbonate, dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane or carbonyl peroxyacid-O,O-(1,1-dimethylpropyl)-O-(2-ethylhexyl) ester or a combination of at least two thereof; Preferably, the auxiliary crosslinking agent includes any one of triallyl isocyanurate, trimethallyl isocyanate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate or propoxylated trimethylolpropane triacrylate, or a combination of at least two thereof.

5. The packaging film according to claim 3 or 4, characterized in that: The silane coupling agent comprises a combination of a first silane coupling agent and a second silane coupling agent; Preferably, in the first auxiliary agent, the content of the first silane coupling agent is 0.1 to 0.5 parts by weight; Preferably, in the first auxiliary agent, the content of the second silane coupling agent is 0.1 to 0.5 parts by weight; Preferably, the first silane coupling agent includes any one or a combination of at least two of 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyltrimethoxysilane, 3-glycidylpropyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, isopropyl triisostearoyl titanate, isopropyl tri(dioctylpyrophosphate) titanate, isocyanatepropyltrimethoxysilane, isocyanatepropyltriethoxysilane or 1,3,5-tris(trimethoxysilylpropyl)isocyanurate; Preferably, the second silane coupling agent is a silane oligomer; Preferably, the silane oligomer includes any one or a combination of at least two of 3-(methacryloyloxy)propyltrimethoxysilane oligomer, vinyltrimethoxysilane oligomer or vinyltriethoxysilane oligomer; Preferably, the tackifier comprises any one or a combination of at least two of toluene diisocyanate, isophorone diisocyanate, isophorone diisocyanate polymer, diphenylmethane diisocyanate, diphenylmethane diisocyanate polymer, hexamethylene diisocyanate or hexamethylene diisocyanate polymer; Preferably, the light stabilizer includes any one of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) succinate or poly-{[6-[(1,1,3,3-tetramethylbutyl)-imino]-1,3,5-triazine-2,4-diyl][2-(2,2,6,6-tetramethylpiperidinyl)-nitrogen]-hexylene-[4-(2,2,6,6-tetramethylpiperidinyl)-amino]} or a combination of at least two thereof.

6. The encapsulation film according to any one of claims 1 to 5, characterized in that: The second auxiliary agent comprises the following components in parts by weight: 0.2 to 1.0 parts of a crosslinking agent, 0.5 to 1.5 parts of a co-crosslinking agent, 0.2 to 1.0 parts of a silane coupling agent, 0.1 to 0.5 parts of a light stabilizer, and 0.1 to 0.5 parts of an ultraviolet light absorber.

7. The packaging film according to claim 6, characterized in that: The crosslinking agent in the second auxiliary agent includes any one or a combination of at least two of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy (2-ethylhexyl) carbonate, dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane or carbonyl peroxyacid-O,O-(1,1-dimethylpropyl)-O-(2-ethylhexyl) ester; Preferably, the auxiliary cross-linking agent in the second auxiliary agent includes any one of triallyl isocyanurate, trimethallyl isocyanate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate or propoxylated trimethylolpropane triacrylate, or a combination of at least two thereof.

8. The packaging film according to claim 6 or 7, characterized in that: The silane coupling agent in the second auxiliary agent includes a combination of a first silane coupling agent and a second silane coupling agent; Preferably, in the second auxiliary agent, the content of the first silane coupling agent is 0.1 to 0.5 parts by weight; Preferably, in the second auxiliary agent, the content of the second silane coupling agent is 0.1 to 0.5 parts by weight; Preferably, the first silane coupling agent in the second auxiliary agent includes any one of 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl methyl trimethoxysilane, 3-glycidyl propyl trimethoxysilane, vinyl trimethoxysilane, 3-aminopropyl triethoxysilane, triisostearoyl isopropyl titanate, isopropyl tris(dioctyl pyrophosphate acyloxy) titanate, isocyanate propyl trimethoxysilane, isocyanate propyl triethoxysilane or 1,3,5-tris(trimethoxysilylpropyl) isocyanurate or a combination of at least two thereof; Preferably, the second silane coupling agent in the second auxiliary agent is a silane oligomer; Preferably, the silane oligomer includes any one or a combination of at least two of 3-(methacryloyloxy)propyltrimethoxysilane oligomer, vinyltrimethoxysilane oligomer, vinyltriethoxysilane oligomer, and isocyanurate silane oligomer; Preferably, the ultraviolet light absorber includes any one of 2-hydroxy-4-n-octyloxybenzophenone, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'bis(a,a-dimethylbenzyl)phenyl)benzotriazole, 2,4-bis(2,4-xylyl)-6-(2-hydroxy-4-n-octyloxyphenyl)-1,3,5-triazine, 2,2-methylenebis[5-(1,1,3,3-tetramethylbutyl)-3-(1,3-dihydrobenzotriazole)phenol] or a combination of at least two thereof; Preferably, the light stabilizer in the second auxiliary agent includes any one of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) succinate or poly-{[6-[(1,1,3,3-tetramethylbutyl)-imino]-1,3,5-triazine-2,4-diyl][2-(2,2,6,6-tetramethylpiperidinyl)-nitrogen]-hexylene-[4-(2,2,6,6-tetramethylpiperidinyl)-amino]} or a combination of at least two thereof.

9. A method for preparing a packaging adhesive film according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: The raw materials for preparing the radiation cross-linked buffer layer and the bonding layer are mixed respectively, co-extruded, cast into films, and then the radiation cross-linked buffer layer is pre-treated by electron beam irradiation to obtain the encapsulation adhesive film; In the electron beam irradiation pretreatment, the irradiation parameters are as follows: voltage is 100-300 KeV, and dosage is 20-60 KGy.

10. An application of the encapsulation film according to any one of claims 1 to 8 in a busbar-free battery assembly; Preferably, the busbar-free battery assembly comprises a glue-point type busbar-free battery assembly.

Citation Information

Patent Citations

  • Packaging adhesive film with different pre-crosslinking degrees and preparation method thereof

    CN112251166A

  • Multi-layer co-extrusion type high-reliability white EVA (Ethylene Vinyl Acetate) adhesive film and preparation method thereof

    CN115926668A

  • Packaging adhesive film and photovoltaic module

    CN116589940A

  • Composite adhesive film for packaging photovoltaic module as well as preparation method and application of composite adhesive film

    CN117683476A

  • Packaging adhesive film for solar module and preparation method of packaging adhesive film

    CN118755403A